Role Of Demographic Factors with The Level of Treatment Compliance in Directly Observed Short Course Chemotherapy - Tiwari, Sonia; Wavare, R R (National Journal of Community Medicine, 2016)
Background: Tuberculosis has claimed more lives than any other scourges of the past. It still remains a major public health problem worldwide. It continues to elude the brightest minds and to challenge human and economic resources of the countries around world. Objective of the study was to assess the role of demographic factors with the level of treatment compliance in DOTS. Materials and methods: The present study was conducted at Sri Aurobindo Medical College and Post Graduate Institute in the Department of Community Medicine from tuberculosis unit in an urban area.The data collection was done with the help of semi-structured questionnaire by interview method. Results: 14 patients up to 25 years completed treatment and there were no defaulters.In the age group 25-45 years 37 patientscompleted treatment in time and 3 became treatment defaulters. Whereas in the age group > 45 years 44 patients completed treatment in time and 8 became treatment defaulters. (P<0.05) Amongst the males 45.16% completed treatment in time and amongst the females 54.83% completed treatment in time. Conclusions: The defaulters were found more in males than females. It was also found 60% families were nuclear and had their own houses and 65% patients were married.